Genome-wide association meta-analysis identifies pleiotropic risk loci for aerodigestive squamous cell cancers - Lesseur, Corina; Ferreiro-Iglesias, Aida; McKay, James D.; Bossé, Yohan; Johansson, Mattias; Gaborieau, Valerie; Landi, Maria Teresa; Christiani, David C.; Caporaso, Neil C.; Bojesen, Stig E.; Amos, Christopher I.; Shete, Sanjay; et al. (PLoS genetics, 2021)
Squamous cell carcinomas (SqCC) of the aerodigestive tract have similar etiological risk factors. Although genetic risk variants for individual cancers have been identified, an agnostic, genome-wide search for shared genetic susceptibility has not been performed. To identify novel and pleotropic SqCC risk variants, we performed a meta-analysis of GWAS data on lung SqCC (LuSqCC), oro/pharyngeal SqCC (OSqCC), laryngeal SqCC (LaSqCC) and esophageal SqCC (ESqCC) cancers, totaling 13,887 cases and 61,961 controls of European ancestry. We identified one novel genome-wide significant ( P meta <5x10 -8 ) aerodigestive SqCC susceptibility loci in the 2q33.1 region (rs56321285, TMEM273 ). Additionally, three previously unknown loci reached suggestive significance ( P meta <5x10 -7 ): 1q32.1 (rs12133735, near MDM4 ), 5q31.2 (rs13181561, TMEM173 ) and 19p13.11 (rs61494113, ABHD8) . Multiple previously identified loci for aerodigestive SqCC also showed evidence of pleiotropy in at least another SqCC site, these include: 4q23 ( ADH1B ), 6p21.33 ( STK19 ), 6p21.32 ( HLA-DQB1 ), 9p21.33 ( CDKN2B-AS1 ) and 13q13.1( BRCA2 ). Gene-based association and gene set enrichment identified a set of 48 SqCC-related genes rel to DNA damage and epigenetic regulation pathways. Our study highlights the importance of cross-cancer analyses to identify pleiotropic risk loci of histology-related cancers arising at distinct anatomical sites.